2018
DOI: 10.3389/fcvm.2018.00152
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Secreted by Hypoxic AC10 Cardiomyocytes Modulate Fibroblast Cell Motility

Abstract: Extracellular vesicles (EVs) are small membrane vesicles secreted by most cell types with important roles in cell-to-cell communication. To assess their relevance in the context of heart ischemia, EVs isolated from the AC10 ventricular cardiomyocyte cell line (CM-EVs), exposed to normoxia (Nx) or hypoxia (Hx), were incubated with fibroblasts (Fb) and endothelial cells (EC). CM-EVs were studied using electron microscopy, nanoparticle tracking analysis (NTA), western blotting and proteomic analysis. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In terms of EV secretion, we observed that MSC-T-HIF c secreted higher amounts of EVs than did MSC-T c without significant alterations in their characteristic features such as size, shape or tetraspanins content ( Figure 4 a–f), in line with our previously published results [ 23 , 24 ]. Next, we measured the immunosuppressive capacity of MSC-T-HIF c -derived EVs (EV MSC-T-HIF c ) in a T-cell proliferation assay.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of EV secretion, we observed that MSC-T-HIF c secreted higher amounts of EVs than did MSC-T c without significant alterations in their characteristic features such as size, shape or tetraspanins content ( Figure 4 a–f), in line with our previously published results [ 23 , 24 ]. Next, we measured the immunosuppressive capacity of MSC-T-HIF c -derived EVs (EV MSC-T-HIF c ) in a T-cell proliferation assay.…”
Section: Resultssupporting
confidence: 92%
“…EVs were isolated using a serial ultracentrifugation protocol [ 24 ]. Briefly, EV-containing supernatants were centrifuged at 2000× g for 20 min (Eppendorf 5804 benchtop centrifuge, A-4-62 rotor), followed by centrifugation at 10,000× g for 70 min (Hitachi CP100NX centrifuge, Beckman Coulter 50.2 Ti rotor) and supernatants were subsequently filtered manually through a 0.22 μm using a syringe.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of EVs secretion by hypoxia, observed in our study, is a common phenomenon, shown, among other cell types, for melanoma, glioblastoma, prostate, ovarian, breast, and lung cancer-derived cells. Also non-cancer cells like cardiomyocytes 34 and renal proximal tubular cells 35 increase EV production upon hypoxic treatment. We found that hypoxia-induced EV production by mouse Renca cells was much stronger as compared to human 786-O cell, which may be related to the differences in HIF signaling in these two cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia also changes the secretion of paracrine factors that are involved in many processes of infarct healing, such as angiogenesis, fibroblast differentiation, and remodeling of the extracellular matrix. Hypoxic cardiac myocytes upregulate vascular endothelial growth factor (VEGF) ( 51 , 52 ), insulin-like growth factor 2 ( 52 ), inflammatory cytokines (TNF-α, IL-1β, IL-6), and TGF-β ( 53 ). As TGF-β is known to promote fibroblast differentiation into myofibroblasts, medium conditioned by hypoxic myocytes has been reported to drive cardiac fibroblast migration ( 54 ) and facilitate faster wound closure in cultured skin fibroblasts ( 53 ).…”
Section: In Vitro Models Of Myocardial Ischemia and Hypoxiamentioning
confidence: 99%
“…Hypoxic cardiac myocytes upregulate vascular endothelial growth factor (VEGF) ( 51 , 52 ), insulin-like growth factor 2 ( 52 ), inflammatory cytokines (TNF-α, IL-1β, IL-6), and TGF-β ( 53 ). As TGF-β is known to promote fibroblast differentiation into myofibroblasts, medium conditioned by hypoxic myocytes has been reported to drive cardiac fibroblast migration ( 54 ) and facilitate faster wound closure in cultured skin fibroblasts ( 53 ). Similar to cardiac myocytes, hypoxic cardiac fibroblasts upregulate TGF-β1 and also its receptor, TGFβ-R1, which can play a role in autocrine signaling pathways to promote fibroblast differentiation ( 46 , 48 ).…”
Section: In Vitro Models Of Myocardial Ischemia and Hypoxiamentioning
confidence: 99%